2019
DOI: 10.1177/0192623319826066
|View full text |Cite
|
Sign up to set email alerts
|

Pathological Safety Assessment in Preclinical Neurothrombectomy Studies

Abstract: The design, production, and preclinical testing of neurothrombectomy devices is in a burgeoning phase as the demand escalates for safe and reliable treatment options following neurovascular stroke. Currently, there is a paucity of published data describing the development of iatrogenic vascular lesions occurring secondary to neurothrombectomy procedures. In an effort to test new devices, demonstrate device safety, satisfy regulatory requirements, and develop an understanding of the potential for associated vas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 39 publications
(78 reference statements)
0
2
0
Order By: Relevance
“…Vessel wall injury, including vessel perforation, artery dissection, endothelial cell damage, secondary intracranial hemorrhage, and vascular stenosis, is a common complication of thrombectomy. 9 , 28 , 29 In this study, the Skyflow device showed excellent flexibility and an appropriate stent size for different vessels to avoid iatrogenic vascular damage. As a result, it achieved good safety with only mild vasospasm on DSA images and no obvious damage to vessel architecture.…”
Section: Discussionmentioning
confidence: 93%
“…Vessel wall injury, including vessel perforation, artery dissection, endothelial cell damage, secondary intracranial hemorrhage, and vascular stenosis, is a common complication of thrombectomy. 9 , 28 , 29 In this study, the Skyflow device showed excellent flexibility and an appropriate stent size for different vessels to avoid iatrogenic vascular damage. As a result, it achieved good safety with only mild vasospasm on DSA images and no obvious damage to vessel architecture.…”
Section: Discussionmentioning
confidence: 93%
“…The U.S. Food and Drug Administration (FDA) recognizes swine as a suitable model for biocompatibility testing and the safety assessment of implanted devices in a variety of organs and systems. 56,130 Coronary stents, 84,93,94 abdominal aortic aneurysm grafts, 154 prosthetic heart valves, 133 abdominal meshes, 53 and neurovascular devices 121 are medical devices that are commonly tested in swine. In addition, temporarily inserted energy-based devices for renal denervation 108 or for cardiac, 124,126 lung, 114 or liver ablations 50 are usually evaluated in swine.…”
Section: Medical Device Testingmentioning
confidence: 99%